Penerapan Filsafat Progresivisme Dalam Pendidikan Agama Islam - Umar, Hanif Umar (Education Management: Jurnal Manajemen Pendidikan Islam, 2023)
The Application of Progressivism Philosophy in Islamic Religious Education is intended to help readers understand the application of Progressivism philosophy in Islamic Religious Education which is explained in detail in Islamic Religious Education. This article uses descriptive qualitative methods. The results of this research show that Islamic education is one of the most important parts of life, because everything we do in the world cannot be separated from the laws established by God. So it is possible that Muslims throughout the world will definitely choose a place to seek as much knowledge about Islamic education as possible. Progressivism is a school of educational philosophy that advocates change and progress in Islamic religious education in accordance with changing times. The goal of progressivism is to produce students who are able to think practically and solve problems effectively in an environment that increasingly develops and advances based on their experience